Willingness to ride and perceptions of autonomous public transit. (August 2020) - Kassens-Noor, Eva; Kotval-Karamchandani, Zeenat; Cai, Meng
Highlights: Examines the views of public transit riders including the mobility-challenged. Determines attitudes towards AVs using a dual sampling survey approach. Provides empirical evidence on AV willingness to ride between fixed-route and demand-response riders. Compares the attitudes of seniors and special needs population, against general public transit riders. Abstract: Autonomous vehicles (AVs) hold great promise to contribute to global sustainability by expanding access to mobility. The introduction of autonomous buses and shuttles could be a turning point for public mobility in the USA, but how autonomous public transit is perceived remains largely unknown. To fill this gap, this study analyzes the willingness to use autonomous buses and shuttles based on two surveys conducted in Michigan. These surveys were a phone-based random-sampling survey of the general public and an on-board intercept survey of public transit riders. We found that autonomous buses might increase willingness to use public transit. 15% of people, who occasionally ride or do not ride public transit, embrace the idea of using autonomous bus service, while fixed-route riders were more likely to accept AVs than demand-response transit riders. However, about half of the public transit riders were hesitant about riding in autonomous buses citing concerns over safety, no human, and distrust in technology. Willingness to ride was higher among younger males than it was for females, seniors, and people with mobility disabilities. In addition, our data suggests that riders' satisfaction with their drivers - be it skill, professionalism, or friendliness - had no impact on willingness to ride in AVs. As AVs become ready for deployment, policymakers and public transportation service providers should consider AV acceptance among vulnerable individuals to bring AV benefits to all.